Lexicons in Nelayan Dance Movements - Ni Ketut Sri Andini (Universitas Nurul Jadid, 2023)
AbstractNelayan dance is one of the classical dances in Bali that have high cultural value. Nelayan dance has unique and varied lexicons to study. Usually, the lexicons in Nelayan dance will be used during dance practice. However, due to the development of the times, the use of the lexicon in the Nelayan dance is decreasing. This study aims to collect the lexicon that exists in the Nelayan dance. This research was designed in a descriptive qualitative form using an ecolinguistic approach. The object of this research is the lexicon of movements in the Nelayan dance, including the cultural meanings of each of the lexicons. The subjects of this study were three informants who had extensive knowledge of the arts. The data from this study were obtained by conducting observations and interviews at the Sanggar Seni Manik Uttara. The results of this study indicate that the total lexicon movements in Nelayan dance are 55 lexicons which are divided into six types, such as head movements (4 lexicons), eye movements (5 lexicons), neck movements (2 lexicons), hand movements (22 lexicons), body movements (14 lexicons), and leg movements (8 lexicons). Based on those lexicons, the cultural meaning found in lexicons’ movements is 28 lexicons.Keywords: Lexicons, nelayan dance, ecolinguistics, movements, language death